The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5194/bg-12-1713-2015
|View full text |Cite
|
Sign up to set email alerts
|

Early spring mesopelagic carbon remineralization and transfer efficiency in the naturally iron-fertilized Kerguelen area

Abstract: Abstract. We report on the zonal variability of mesopelagic particulate organic carbon remineralization and deep carbon transfer potential during the Kerguelen Ocean and Plateau compared Study 2 expedition (KEOPS 2; OctoberNovember 2011) in an area of the polar front supporting recurrent massive blooms from natural Fe fertilization. Mesopelagic carbon remineralization (MR) was assessed using the excess, non-lithogenic particulate barium (Ba xs ) inventories in mesopelagic waters and compared with bacterial pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
58
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(71 citation statements)
references
References 77 publications
(129 reference statements)
11
58
2
Order By: Relevance
“…The upper mesopelagic depletion horizon observed over most of the sections would indicate that regeneration of organic material occurs at these depths as commonly observed in most oceanic basins [Dehairs et al, 1997[Dehairs et al, , 2008Jacquet et al, 2007bJacquet et al, , 2011Jacquet et al, , 2015. The upper mesopelagic depletion horizon observed over most of the sections would indicate that regeneration of organic material occurs at these depths as commonly observed in most oceanic basins [Dehairs et al, 1997[Dehairs et al, , 2008Jacquet et al, 2007bJacquet et al, , 2011Jacquet et al, , 2015.…”
Section: [D_ba Cons ] Versus [D_ba Nc ]: a Tale Of Two (Temporal) Scalesmentioning
confidence: 77%
See 1 more Smart Citation
“…The upper mesopelagic depletion horizon observed over most of the sections would indicate that regeneration of organic material occurs at these depths as commonly observed in most oceanic basins [Dehairs et al, 1997[Dehairs et al, , 2008Jacquet et al, 2007bJacquet et al, , 2011Jacquet et al, , 2015. The upper mesopelagic depletion horizon observed over most of the sections would indicate that regeneration of organic material occurs at these depths as commonly observed in most oceanic basins [Dehairs et al, 1997[Dehairs et al, , 2008Jacquet et al, 2007bJacquet et al, , 2011Jacquet et al, , 2015.…”
Section: [D_ba Cons ] Versus [D_ba Nc ]: a Tale Of Two (Temporal) Scalesmentioning
confidence: 77%
“…Among these biogeochemical tracers, particulate biogenic barium (P_Ba barite-BaSO 4 ) is one of the few proxies used to estimate organic carbon remineralization in the mesopelagic interior (100-1000 m) [Dehairs et al, 1980[Dehairs et al, , 1997[Dehairs et al, , 2008Cardinal et al, 2001Cardinal et al, , 2005Jacquet et al, 2005Jacquet et al, , 2007aJacquet et al, , 2008aJacquet et al, , 2008bJacquet et al, , 2011Jacquet et al, , 2015Stroobants et al, 1991]. Studies have shown that in a global ocean undersaturated with respect to barite [Monnin et al, 1999;Monnin and Cividini, 2006], P_Ba barite mainly precipitates in the mesopelagic zone inside oversaturated biogenic microenvironments during organic matter degradation by marine prokaryotes [Dehairs et al, 1980[Dehairs et al, , 1997Collier and Edmond, 1984;Bertram and Cowen, 1997;Bishop, 1988;Ganeshram et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…5). The sampling being done during the early stages of bloom development, it is likely that an accumulation of biomass in surface waters could limit the export (Jacquet et al, 2015;Planchon et al, 2015). Indeed, the lowest ThE PN and ThE BSi were recorded at A3-2, E-4W and F-L stations, confirming that only a small fraction of the produced biomass was exported.…”
Section: Cruisementioning
confidence: 95%
“…The organic C content of sinking particulate matter is also impacted by remineralization (Jacquet et al, 2015). Using BSi:POC and BSi:PN ratios, the POC and PN degradation relative to BSi is reflected in the increase of ratios with depth (Fig.…”
Section: Fluxes and Degradation Of Sinking Particlesmentioning
confidence: 99%
“…Low export efficiency suggests that the products of primary production are mainly recycled within the mixed layer by an efficient microbial loop (Sarthou et al, 2008;Obernosterer et al, 2008;Christaki et al, 2014;Malits et al, 2014). The carbon sequestration efficiency induced by iron fertilization remains proportionally relatively low (Jacquet et al, , 2015.…”
Section: High Primary Production In Naturally Iron-fertilized Bloomsmentioning
confidence: 99%